Design and Synthesis of New Selective P-gp Substrates and Inhibitors - Cantore, Mariangela; Leopoldo, Marcello; Berardi, Francesco; Perrone, Roberto; Colabufo, Nicola Antonio (Current Pharmaceutical Design, 2016)
P-glycoprotein is an ATP-binding cassette transporter involved in drug absorption, distribution and excretion. It pumps a wide range of xenobiotic compounds out of the cells and plays a crucial role in Multi Drug Resistance. Moreover, recent studies have demonstrated that changes in P-gp function and/or expression at the blood brain barrier are implicated in the pathogenesis of neurological disorders such as therapy-refractory epilepsy, Alzheimer’s and Parkinson’s disease. In the last decades the studies have been addressed to the discovery of potent P-gp inhibitors able to revert pharmacoresistance and to the development of PET tracers to detect P-gp activity and expression for an early diagnosis and therapy monitoring of neurodegenerative disease. However, clinical trials have reported only limited success in reversing MDR and radiolabeled ligands were not actually useful to study differences of transporter function in different brain regions due to their low brain uptake. The difficulties into the discovery of new ligands is due to the use of different experimental assays, to the fact that P-gp is highly flexible protein with different binging sites and available crystallographic structures for the protein have inadequate resolution. To overcome these limitations research groups prefer computational approaches such as homology models in their structure-based design or ligand-based methodologies. A recent approach aimed to identify ligands which can interrupt ATP-binding and hydrolysis by P-gp, by interacting at the NBDs of the protein. In this review results from radiolabeled, substrates and inhibitors, for monitoring the activity and expression of P-gp, respectively, are presented.
Keywords: ligand-based models